A COMPARISON BETWEEN THE SPATIAL CONSIDERATIONS OF TECHNOLOGIES IN STANDARD AND HYBRID OPERATING ROOMS - Mohamed, Mohamed Saber; Abdou, Mohamed Said (MATTER: International Journal of Science and Technology, 2021)
The spatial considerations of operating rooms (ORs) are evolving frequently to keep pace with the scientific development of surgical procedures. The study utilizes a comparative approach to specify the differences between the dimensional and spatial considerations of equipping standard ORs that introduced significant technological improvements and hybrid ORs that integrate developed imaging equipment within the surgical environment. For example, operating tables offer a wide range of tilting angles and a radiolucent surface to pass-through x-rays in the hybrid OR, while the articulating arms of ceiling-mounted booms need enough space to move freely within the OR and suitable load capacity to hold various medical utilities. On the other hand, devices such as anesthesia and heart-lung machines are placed near the patient to provide the required medical support, while imaging equipment in hybrid ORs such as the C-arm require specific spatial considerations for ergonomic workflows. Ultimately, spatial considerations of hybrid ORs are similar to standard ORs with unique intraoperative imaging technologies.